Toward a centrality index for computing grids - Mourão, Paulo (2012)
The computing grid has emerged as an attractive field in Computer Science. However, little attention has focused on the centrality of each computing grid. In this article, we suggest a Centrality Index based on the economist and geographer Walter Christaller’s Central Place Theory. With a Centrality Index, each grid can be evaluated in terms of function concentration and user distribution.